THE EFFECT of PENCAK SILAT SPORTS on PREMENSTRUAL SYNDROME IN FEMALE STUDENTS of THE PENCAK SILAT STUDENT ACTIVITY UNIT at dr. SOEBANDI UNIVERSITY - Herlidian Putri; Ai Nur Zannah (Journal for Quality in Women's Health, 2023)
The purpose of this study was to determine the effect of pencak silat exercise on premenstrual syndrome (PMS) in female students of UKM Pencak Silat. This design is correlational analytic with cross sectional method. The population in study were all female members of UKM Pencak Silat University of dr. Soebandi Jember. The sample size in this study was 30. The statistical test is Spearman Rank. There are a large proportion of respondents with sufficient pencak silat sports (56.7%). Most of the respondents (56.7%) did not experience Premenstrual Syndrome (PMS) in the mild category. The results of the Spearman rank test obtained p value of 0.000 below the value of α (0.05), which means that Ha is accepted. . There is an influence of pencak silat exercise on premenstrual syndrome (PMS) in female students of UKM Pencak Silat University, dr. Soebandi Jember